RESILIENSI PENERIMA MANFAAT MENGIKUTI PEMBELAJARAN KETERAMPILAN DI PANTI SOSIAL BINA REMAJA (PSBR) RUMBAI PEKANBARU - Lestari, Dela Octa Indah; ayub, Daeng; Irja, Desti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem formulation in this research is how well beneficiary resilience follow skill learning at Teenage Social Institution (PSBR) Rumbai Pekanbaru? How big is the contribution of beneficiary resilience following skill learning at Teenage Social Institution (PSBR) Rumbai Pekanbaru? The benefit of this research is to know the level of beneficiary resilience following skill learning at Teenage Social Institution (PSBR) Rumbai, Pekanbaru. This research is descriptive research with quantitative approach. The population in this study were all beneficiaries who followed the skills training at Teenage Social Institution (PSBR) Rumbai Pekanbaru which amounted to 70 respondents. The sampling technique in this research is using the technique of saturated samples (Survei) is the taking of sample members of the population done as a whole regardless of the strata that exist in the population. The instruments in this study were questionnaires or questionnaires containing statements about beneficiary resilience following skill learning at the Tribe Sosail Bina Remaja (PSBR) Rumbai Pekanbaru with indicators 1) Internal Control Lectures, 2) Autonomous, 3) Optimism, 4) Flexibility, 5) Motivation, 6) Confidence. Mean confident with mean 4.41 and SD 0.37 then motivation with mean 4.31 and SD 0.34, then optimism with mean 4.28 and SD 0.44, then internal control locus with mean 4.20 and SD 0 , 31, then flexibility with mean 4.12 and SD 0.31 and after that the mean is low is autonomous with mean of 3.98 and SD 0.31. Its meaning is autonomous not very influential to beneficiary resilience. However, confidence is very influential on resilience.Keywords : Resilience, Beneficiaries